A Home for Life or a Home for Now? Understanding Indifference toward Accessibility and Adaptability Features among Some Older Homebuyers. Issue 4 (1st October 2020) - Aitken, Dominic; Gilroy, Rose; Willis, Ken
Abstract: It has been argued that new homes should be designed with greater accessibility and adaptability to meet the needs of ageing populations and that future proofed dwellings may have a marketing edge and be desirable among older people. Drawing on focus groups with recent and prospective older homebuyers and applying an analytical framework based on insurance theory, we identify attitudes toward accessibility and adaptability features which contribute explanations for the indifference of some older people to inclusive design. We argue that without engaging with these perspectives, efforts to improve later life through home design may be inefficient in achieving success.